The Impact of the Increase of Oil Fuel Price and Government Subsidy on Indonesia’s Economic Performance - Akhmad, Akhmad; Asse, Ambo; Nursalam, Nursalam; Ibrahim, Ibrahim; Bunyamin, Bunyamin; Ansaar, Ansaar; Sahajuddin, Sahajuddin (International Journal of Energy Economics and Policy, 2023)
The policy of increasing domestic fuel oil, as a consequence of rising world oil prices, has resulted in changing economic conditions, bearing in mind that oil prices and production are wrong macroeconomic assumptions and are included in the State Revenue and Expenditure Budget. This study aims to determine the impact of rising fuel prices and government subsidies on Indonesia's economic performance. The data used in this study are time series data from 2000 to 2022. Data were obtained from the Indonesian Central Bureau of Statistics, the Ministry of Energy and Mineral Resources, the Ministry of Finance, and Bank Indonesia. This study uses an econometric model using a system of simultaneous equations. The research results show that; The main factors that caused the increase in domestic fuel prices, including crude oil prices, gasoline, diesel, kerosene and aviation fuel, were the increase in world oil prices and the previous year's oil prices. The estimation results also show that the increase in gasoline and diesel fuel can increase the number of poor people, unemployment and inflation in Indonesia. The policy simulation results show that the increase in oil prices has a significant impact on increasing the number of poor people, increasing unemployment and inflation, if this increase is not followed by subsidies in the form of non-energy.